OPTIMALISASI PERAN PEREMPUAN D0ALAM LITERASI KONSUMEN CERDAS INDONESIA - Handayani, Widya Marthauli (Universitas Muara Bungo, 2024)
Understand the relationship between consumers and women. consumers are basically people. People who carry out consumption activities for goods and / or services circulating in the community. In law, people are qualified as legal subjects. One of the legal subjects is a natural person (natuurlijke persoon). Some research results show that the role of women affects income, purchasing decisions, consumption and the household economy. This research aims to provide a comprehensive insight into how the role of women can be optimized in consumer literacy in Indonesia. This research applies normative juridical methodology by integrating various analytical methods, such as comparative, conceptual, and statutory approaches. The research mainly focuses on analytical descriptive specifications, which provide detailed descriptions of the data collected to obtain an in-depth understanding of certain legal events in society. The result of this research is that as women and law-aware family activists, it is important to increase literacy about consumer protection. This can be started by reading related regulations, and participating in legal socialization to protect ourselves and those closest to us in consuming the goods or services we choose.